2001
DOI: 10.4049/jimmunol.166.5.3410
|View full text |Cite
|
Sign up to set email alerts
|

C5a and C5adesArg Enhance the Susceptibility of Monocyte-Derived Macrophages to HIV Infection

Abstract: Mononuclear phagocytes, which include circulating blood monocytes and differentiated tissue macrophages, are believed to play a central role in the sexual transmission of HIV infection. The ability of HIV to productively infect these cells may be influenced by action of exogenous or host-derived substances at the site of viral entry. Given the potent capacities of inflammatory mediators to stimulate anaphylatoxic and immunomodulatory functions in mucosa, the effects of complement-derived anaphylatoxins on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
1
34
0
3
Order By: Relevance
“…C5a is significantly more powerful than C3a in inducing biologically relevant responses [2]. C5a plays an important role in promoting (1) chemotaxis to a variety of leucocytes, including neutrophils and macrophages [3e5]; (2) activation of the respiratory burst in phagocytes [6]; (3) the expression of tumor necrosis factor (TNF)-a and interleukin (IL)-6 in monocytederived macrophages [7] as well as the expression of IL-1b, RANTES and IL-8 in umbilical vein endothelial cells [8]; (4) production of prostaglandins and eicosanoids [9]; (5) release of histamine by mast cells and basophils [10,11]; (6) up-regulation of Fc, complement receptor type 3 (CR3) [12,13] and P-selectin [14]. C5a has also been demonstrated to have an influence in adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…C5a is significantly more powerful than C3a in inducing biologically relevant responses [2]. C5a plays an important role in promoting (1) chemotaxis to a variety of leucocytes, including neutrophils and macrophages [3e5]; (2) activation of the respiratory burst in phagocytes [6]; (3) the expression of tumor necrosis factor (TNF)-a and interleukin (IL)-6 in monocytederived macrophages [7] as well as the expression of IL-1b, RANTES and IL-8 in umbilical vein endothelial cells [8]; (4) production of prostaglandins and eicosanoids [9]; (5) release of histamine by mast cells and basophils [10,11]; (6) up-regulation of Fc, complement receptor type 3 (CR3) [12,13] and P-selectin [14]. C5a has also been demonstrated to have an influence in adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Both C5a and C5a desArg bear similar efficacy at inducing histamine and leukotriene C4 release by primed basophils (8), calcium mobilization in mouse peritoneal macrophages (46) and neutrophil-mediated platelet aggregation (47). Further, both proteins are able to prime macrophages and enhance their susceptibility to HIV infection (48). Therefore, C5a desArginduced cell responses are critically dependent on the type of cell and response studied (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be blocked using a C5aR1-specific mAb. 12 In search for mechanisms underlying this effect, the authors found that C5a increased TNF-a and IL-6 production from MDM. Furthermore, they have shown that specific targeting of C5aR1, using the same mAb that we have used in our study (S5/1), inhibited the C5a-mediated increase of TNF-a or IL-6, demonstrating that C5aR1 signaling is critical for the effect.…”
Section: C5ar Facilitates Ccr5-mediated Hiv Entry Into Differentiatedmentioning
confidence: 99%
“…11 Previous studies have shown that C5a can enhance the infection of MDM and T cells indirectly through the production of interleukin (IL)-6 and tumor necrosis factor (TNF)-a and the attraction of DCs. 10,12 Complementmediated enhancement of HIV infection was also described for CD4 cells. 13 Interestingly, C5aR1 forms heterodimers with the chemokine receptor CCR5, a major coreceptor for viral entry for R5 strains 14 in a rat basophilic leukemia cell line.…”
Section: Introductionmentioning
confidence: 99%